Enhancing physical sciences performance through formative assessment strategies - Mngomezulu, Halalisani; Ramaila, Sam (African Perspectives of Research in Teaching and Learning Journal, 2024)
This study explored the impact of integrating formative assessment practices on improving academic performance among learners in Physical Sciences classrooms. Simple random sampling was utilised in the UMkhanyakude District of KwaZulu-Natal Province, South Africa, to select participants. A quasiexperimental design employing pretest and post-test comparisons was employed, with five secondary schools involved, three comprising an experimental group and two forming a control group. A total of 175 Grade 10 Physical Sciences learners from the selected schools participated in the study. Three teachers from experimental schools underwent training in utilising formative assessment practices, while two teachers from the control group continued with their regular instructional methods without exposure to formative assessment practices. The study was guided by the Assessment for Formative Purpose Cycle as a conceptual framework to explore how formative assessment practices could enhance academic achievement. Data analysis was conducted using SPSS Version 26, employing a 2-way ANOVA statistical technique. Results indicated that students from experimental schools, where the intervention was implemented, demonstrated significantly higher performance compared to those from control schools following standard classroom instruction. The findings suggest the importance of integrating formative assessment practices into the teaching of Physical Sciences within the South African education system to improve learners' conceptual understanding and foster independent learning in the subject.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 8, 2024
Keywords: Academic Performance; Physical Sciences; Formative Assessment; Teaching Strategies; Learning Approaches; Academic achievement; Physical Sciences; Physical science -- Study and teaching